RADEN AYU PEMECUTAN - Ni Made Krisna Dwi Yanti; Tjok Istri Putra Padmini; I Gede Oka Surya Negara (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
The work of dance created by Raden Ayu Pemecutan is a dance pulled by seven princess dancers in the form of a new dance and raises the character of a delicate princess by highlighting the ges-the prayer moves that have been developed and reproduced. In raden ayu siti khotijah’s story, this misunderstanding is explained, because at the moment that Raden Ayu Siti Khotijah was carrying out his prayers and was seen by one instructor who thought Raden Ayu Siti Khotijah was practicing the black arts, and then one day he reported directly to king Kyai Anglurah Pemecutan III and ordered him to kill Raden Ayu Siti Khotijah.The application of Raden Ayu Pemecutan inventiveness of cane using concepts of agem, boiler, badminton, and tangle. With a princess’s subtle concept of dance developed and reinfused it into a movement-an innovative move as an identity to the work itself. The resulting musical accompaniment includes a musical accompaniment coupled with a tambourine instrument as well as with a red, white batik and green batik dress as the identity of the strip. It was created through the method of creation in the stages of exploration, improvisation and formation of the method of creation by Alma m. Hawkins. As for some of the theories used in accomplishing this work are like the theory of creative processes, the theory of imagination and aesthetic theory.Through this work gives one a contemplative and an example of keegKey words: dance to creation, princess smooth, Raden Ayu Pemecutan